2020
DOI: 10.3390/molecules25020317
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Chemical Profiling and Monacolins Quantification in Red Yeast Rice Dietary Supplements by 1H-NMR and UHPLC-DAD-MS

Abstract: Red yeast rice dietary supplements (RYR DS) are largely sold in Western countries for their cholesterol-lowering/regulating effect due to monacolins, mainly monacolin K (MK), which is, in fact, lovastatin, the first statin drug on the market. 1H-NMR was used as an easy, rapid and accurate method to establish the chemical profiles of 31 RYR DS and to quantify their monacolin contents. Among all the 1H resonances of the monacolins found in RYR, only those of the ethylenic protons of the hexahydronaphthalenic rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…Furthermore, the lack of a strict control by food and drug regulatory organs can lead to the marketing of products that, especially in the case of herbal nutraceuticals, might have been scarcely characterized in terms of their contents of potential bioactive (and potentially harmful) components [26]. As already highlighted by other authors, these issues frequently occur for food supplements with lipid-reducing properties, such as those containing RYR and BBR as the main active ingredients [17,18]. Commercial RYR powders and extracts often present scarce standardization of MK and other potentially bioactive monacolins, whose bioactivity and safety have not been well-established yet [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the lack of a strict control by food and drug regulatory organs can lead to the marketing of products that, especially in the case of herbal nutraceuticals, might have been scarcely characterized in terms of their contents of potential bioactive (and potentially harmful) components [26]. As already highlighted by other authors, these issues frequently occur for food supplements with lipid-reducing properties, such as those containing RYR and BBR as the main active ingredients [17,18]. Commercial RYR powders and extracts often present scarce standardization of MK and other potentially bioactive monacolins, whose bioactivity and safety have not been well-established yet [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, natural extracts often lack standardization of the main bioactive compounds, and this leads to a large variability of their amounts per serving, which could cause a lack of efficacy of the dietary supplements or, even worse, to unpredictable side effects [12]. Regarding nutraceuticals with lipid-lowering activity, articles published in the last 10 years have confirmed the heterogeneity of the products available on the market and the lack of standardization of the bioactive ingredients, showing frequent discrepancies between the amounts of bioactives reported by the manufacturers and those detected by the analysis of the same products [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 84 MLs have been identified, though not all of the MLs have been studied . MLs, for instance, monacolin L, monacolin J, dihydromonacolin L, monacolin X, and compactin, etc., in both the lactone and acid forms have attracted more attention, owing to their high contents in FRMR and their well-known beneficial bioactivities (Endo and Hasumi, 1985;Endo, 1985a,b;Endo et al, 1986;Dhale et al, 2007a,b;Zhu et al, 2012;Hachem et al, 2020). With the progress in research on these compounds, more and more MLs have been isolated and characterized.…”
Section: Functional Substances In Frmrmentioning
confidence: 99%
“…All these new analytical methods accelerate the research and make the potential targets available in the near future. Hachem et al [17] reported an easy, rapid and accurate 1 H-NMR analytical method to establish the chemical profiles of red yeast rice dietary supplements and to quantify their monacolin contents. The total content of monacolin was close to that measured by UHPLC, as shown by the good linear correlation between the two sets of values.…”
mentioning
confidence: 99%